Nhận thấy x=0, y= 0 không là nghiệm của hệ. Xét [tex]xy\neq 0[/tex]
Chia các vế của từng pt trong hệ cho [tex]xy[/tex]
HPT[tex]\Leftrightarrow \left\{\begin{matrix} &\frac{x^{2}}{y}+2\frac{y^{2}}{x}=2+\frac{1}{xy} \\ & \\ &\frac{x^{2}}{y}+\frac{y^{2}}{x}=3-\frac{1}{xy} \\ & \end{matrix}\right.[/tex]
[tex]\frac{x^{2}}{y}=u,\frac{y^{2}}{x}=v\Rightarrow \frac{1}{xy}=\frac{1}{uv}[/tex]
Hệ pt trở thành:
[tex]\left\{\begin{matrix} &u+2v=2+\frac{1}{uv} \\ & \\ &u+v=3-\frac{1}{uv} \\ & \end{matrix}\right.[/tex]
Bây giờ giải dễ hơn rồi